PENGEMBANGAN PENDIDIKAN ASWAJA SEBAGAI STRATEGI DERADIKALISASI - Ngainun Naim (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
This study discussed about the role of Aswaja lesson in the efforts of de-radicalization. Radicalization had been more and more evolved since after the fall of New Order. Reformation Era opened wide varieties of expression, included religious expression. The development of radicalization led to widespread of social unrest. Responses appeared, included using the counter-ideology. Aswaja was believed as being able to prevent the proliferation of radicalization. The data presented in this article was derived from observation, interview and review of the literature related to the topic of writing. The argument developed in this paper is that the reconstruction and actualization of the values contained in Aswaja might be personally internalized firmly. An important strategy that might be applyed to disseminate and internalize Aswaja is through education. In the schools in which applying Aswaja lesson, students had the opportunity to have a moderate religious understanding and avoid radicalization.